Upper semicontinuity of random attractors for non-compact random dynamical systems - Bixiang Wang (Electronic Journal of Differential Equations, 2009)
The upper semicontinuity of random attractors for non-compact random dynamical systems is proved when the union of all perturbed random attractors is precompact with probability one. This result is applied to the stochastic Reaction-Diffusion with white noise defined on the entire space R^n.